Faktor-Faktor yang Mempengaruhi Struktur Modal Perusahaan - Wahyuni Suciati; Sri Laksmi Pardanawati; Yuwita Ariessa Pravasanti (Nur Science Institute, 2022)
The purpose of this study is to describe the influences of profitability, the asset structure, and firm size on capital structure of manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The sampling method in this study is purposive sampling technique 4 criteria, and total sample are 77 companies. The data collection technique is secondary data from annual reports. The data collection technique is secondary data from annual reports. This study uses multiple regression analysis. The analysis technique used in this research is descriptive analysis, classical assumption test, data regression analysis, coefficient of determination and hypothesis. Based on the results of data processing shows that profitability has no effect on the capital structure. Asset structure has a significant positive effect to the capital structure. Firm size has a significant positive effect to the capital structure. The results showed that simultaneously profitability, asset structure, and firm size had an effect to the capital structure.